Evaluation of the Bruker Biotyper Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry System for Identification of Aspergillus Species Directly from Growth on Solid Agar Media - Li, Ying; Wang, He; Zhao, Yu-Pei; Xu, Ying-Chun; Hsueh, Po-Ren (Frontiers in Microbiology, 2017)
We evaluated the accuracy of the Bruker Biotyper matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS) system at identifying clinical isolates of Aspergillus species that were grown on agar media. A total of 381 non-duplicate Aspergillus isolates representing 21 different Aspergillus species identified by molecular analysis were included in this study. The Bruker Biotyper MALDI-TOF MS system was able to identify 30.2% (115/381) of the isolates to the species level (score values of 2.000) and 49.3% to the genus level (score values of 1.700-1.999). When the identification cutoff value was lowered from 2.000 to 1.700, the species-level identification rate increased to 79.5% with a slight rise of false identification from 2.6% to 5.0%. From another aspect, a correct species-level identification rate of 89% could be reached by the Bruker Biotyper MALDI-TOF MS system regardless of the score values obtained. The Bruker Biotyper MALDI-TOF MS system had a moderate performance in identification of Aspergillus directly inoculated on solid agar media. Continued expansion of the Bruker Biotyper MALDI-TOF MS database and adoption of alternative cutoff values for interpretation are required to improve the performance of the system for identifying highly diverse species of clinically encountered Aspergillus isolates.